A Summary of Selected Legislation Relating to the Handicapped 1972 - Department of Health, Education, and Welfare, Washington, DC.; Department of Health, Education, and Welfare, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Summarized are 11 legislative acts benefiting the handicapped and enacted by the 92nd Congress (1971-1972). Given for each act is the title, public law number, and a summary of the law's general scope. Listed as major legislation benefiting the handicapped are the Social Security Amendments of 1972, the Intermediate Care Amendments of 1971, the Wagner-O'Day Amendments, and the Economic Opportunity Amendments of 1972. Also summarized is other legislation benefiting the handicapped including the Military Medical Benefits Amendments, the Revenue Act of 1971, the Education Amendments of 1972, the Social Security Benefit Increase, the Maternal and Child Health Amendments, the Rights of the Blind and Other Physically Handicapped Persons in the District of Columbia act, and the bill establishing the National Advisory Commission on Multiple Sclerosis. Appended are a chart detailing the legislative history of the 11 laws and cross references to original legislative acts of amendment bills. (DB)
Availability: Superintendent of Documents, U.S. Gov't Printing Office, Washington, D.C. 20402 ($0.40).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Exceptional Child Services; Federal Legislation; Handicapped Children